2016
DOI: 10.1016/j.thromres.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant drug level testing in clinical practice: A single institution experience

Abstract: We performed a review of all direct oral anticoagulant (DOAC) levels – ecarin times for dabigatran and anti-Xa levels for rivaroxaban and apixaban – ordered at our institution with the purpose of evaluating DOAC levels from “real-world” (non-clinical trial) patients taking DOACs long-term, in order to assess levels obtained, reasons for checking levels, and actions taken based on the testing result. A total of 28 patients had 48 levels sent over a 36-month period. The majority of outpatient levels were within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
(23 reference statements)
1
38
0
3
Order By: Relevance
“…In spite of these limitations, our study, together with the report of Martin and Moll, casts light on the use of DOAC measurement in real‐world clinical practice. Key observations include the relative infrequency with which measurement is requested, common indications for testing in the inpatient (surgery, breakthrough thrombosis, bleeding) and ambulatory settings (extremes of bodyweight, suspected malabsorption), and the role drug levels may play in patient management.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In spite of these limitations, our study, together with the report of Martin and Moll, casts light on the use of DOAC measurement in real‐world clinical practice. Key observations include the relative infrequency with which measurement is requested, common indications for testing in the inpatient (surgery, breakthrough thrombosis, bleeding) and ambulatory settings (extremes of bodyweight, suspected malabsorption), and the role drug levels may play in patient management.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, real‐world clinical experience with laboratory measurement of DOACs at only one other institution has been published. Martin and Moll reported on 48 DOAC levels in 28 patients at the University of North Carolina (UNC) Chapel Hill . They too found that DOAC measurement was uncommon and was reserved for special circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…9 No therapeutic ranges for DOACs have been published based on the results of clinical trials and potential interferences by clinical and laboratory parameters have not been well characterized. 10,11 Manufacturers and previous reports provide only peak and/or trough plasma concentrations as determined by liquid chromatography/tandem mass spectrometry (LC-MS/MS), and thus, term of ontherapy range was used in the current study, as has been previously described. 10,12 Liquid chromatography/tandem mass spectrometry is the gold standard method for measuring plasma DOAC levels, but DOAC levels vary widely from trough to peak among individualpatients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous retrospective real-world studies of the utility of DOAC levels have found that levels are infrequently requested and are of limited utility. 36,37 However, this may reflect a lack of clinician awareness of the availability of these tests, the long TAT and an unfamiliarity with result interpretation. 36 In contrast, in our study, DOAC levels were widely used and influenced clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 However, this may reflect a lack of clinician awareness of the availability of these tests, the long TAT and an unfamiliarity with result interpretation. 36 In contrast, in our study, DOAC levels were widely used and influenced clinical decision making. This may be because of our relatively quick TAT, clinician awareness and Our study has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%